Developing an integrated management system for western flower thrips, Frankliniella occidentalis (Pergande), on deciduous fruit, using semiochemicals in a push-pull strategy - Allsopp, Elleunorah (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.